Razvoj žil - Petrovič, Danijel (Medicinski razgledi, 2003)
The first evidence of blood vessel formation can be detected in the splanchnopleuric mesoderm of the yolk sac (extraembryonic mesoderm) on day 17,and in the splanchnopleuric mesoderm of the embryonic disc on day 18, when the embryo is no longer able to satisfy its nutritional requirements by diffusion alone. The vascular system is derived from the mesoderm (mainly the splanchnic mesoderm), and the development of the, vascular system is affected by the endoderm. In the third week, the primordial heart and arterial system appear. In the fifth week, three pairs of important veins cari be recognized: the vitelline or omphalomesenteric, the urnbilical and the common cardinal veins, which flow into the sinus venosus. The lymphatic system begins to develop from the splanchnopleuric mesoderm in the fifth week.
Keywords: Aorta; Blood Vessels; Embryology; Aorta, Thoracic; Krvne žile; Lymphatic System; Limfatični sistem; Arteries; Aorta torakalna; Veins; Arterije; Vene; ožilje; žile; embriologija; razvoj